1977
DOI: 10.1172/jci108703
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of antibody to capsular polysaccharide in infection with type III strains of group B Streptococcus.

Abstract: A B S T R A C T The development of antibody in response to invasive infection with type III strains of group B Streptococcus was studied in sera from 31 infants and 4 adults by means of a quantitative radioactive antigen-binding assay. Low concentrations of antibody were consistently found in the acute sera of patients who developed clinical illness. Although adults with puerperal sepsis and infants with bone or joint infection uniformly demonstrated significant rises in serum antibody concentration after reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

1980
1980
1985
1985

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(69 citation statements)
references
References 28 publications
3
64
0
2
Order By: Relevance
“…Since susceptibility to invasive infection in mice (4) and in human infants (6,23,24) correlates with low levels of serum antibody directed against the type-specific antigens of GBS, one proposed method for the prevention of neonatal disease is active immunization of child-bearing age women with these polysaccharides. This method presumes immunogenicity and safety of candidate vaccines, induction of IgG class antibody to insure placental transport, and protection by these maternally derived antibodies in neonates susceptible to invasive infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since susceptibility to invasive infection in mice (4) and in human infants (6,23,24) correlates with low levels of serum antibody directed against the type-specific antigens of GBS, one proposed method for the prevention of neonatal disease is active immunization of child-bearing age women with these polysaccharides. This method presumes immunogenicity and safety of candidate vaccines, induction of IgG class antibody to insure placental transport, and protection by these maternally derived antibodies in neonates susceptible to invasive infection.…”
Section: Discussionmentioning
confidence: 99%
“…This method presumes immunogenicity and safety of candidate vaccines, induction of IgG class antibody to insure placental transport, and protection by these maternally derived antibodies in neonates susceptible to invasive infection. For type III GBS the first two requirements have been experimentally verified (24,25), although protective efficacy remains to be documented. Although little is known about human immunity to other serotypes of GBS, careful immunologic and chemical characterization of their surface antigens has served as a major approach to vaccine development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…he concentration of antibody to native type Ia or 111 GBS polysaccharides in adult or neonatal human sera and in GPS was determined by a radioactive antigen-binding assay described previously (8,9). Antigens used in the present studies were purified native type 111 and type I11 capsular polysaccharides intrinsically labeled with I3H].…”
Section: Isolation Of Pmnmentioning
confidence: 99%
“…Therefore, susceptibility to invasive GBS disease may not be related just to the level of antibody in serum, but also to the characteristics of the invading GBS. Using a radioimmunoassay to measure antibody to GBS, Baker et al (6) found mothers of infants with type 111 disease to have a lower median antibody level as compared to antibody levels in mothers with healthy infants. However, there were wide ranges in antibody concentrations in each group.…”
Section: M891mentioning
confidence: 99%